Determinação do potencial fisiológico de sementes de arroz baseado na integridade das membranas celulares - Barbieri, Ana Paula Piccinin (2011)
Appropriate procedures for analyze the quality of seed is of fundamental importance, but are still incomplete in the quality control programs. The work was aims to standardize the methodology of the electrical conductivity mass and individual test and potassium leachate test to evaluate the vigor of rice seeds. It was used ten lots of rice seeds produced in the 2008/2009 crop, five the IRGA 424 variety and five Puita Inta CL variety.The lots were initially characterized the following determinations and tests: water content, germination test, first count, cold germination, length and biomass dry of seedlings and field emergence. For the electrical conductivity mass test variations were studied: number of seeds (25 and 50), water volume (50 and 75 ml), presence or absence of bark and immersion periods (1, 2, 4, 8, and 24 hours), temperature of 25 ºC. In the conductivity test individually survey the same periods of seeds immersion with and without bark, at a temperature of 25ºC and Seed Automatic Analyzer SAD 9000-S. It was also determined the amount of potassium leachate in the immersion solution, through flame photometer in different periods of immersion (30, 60, 90, 120, 150 and 180 minutes). It was concluded that the electrical conductivity mass test and individual is promising for the separation of lots of rice depending on the vigour of the seeds, but in the two ways of applying has influence the genotype used. For variety IRGA 424, the best conditions for the realization of the electrical conductivity mass test is the use of 25 seeds with bark, immersed in 50 or 75 mL of distilled and deionised water for 2 to 8 hours at 25ºC. For the evaluation of individual electrical conductivity the use of seeds with bark immersed for a period of 24 hours is appropriate. To the potassium leakage test the correct procedure to classify lots of rice seeds at function their physiological quality, is the combination 50 pure seeds submerged in 50 mL of distilled and deionized water at 25ºC for 60 minutes.